EKSPLORASI BIBLIOMETRIK BERDASARKAN DATA SCOPUS (2013-2023): HUBUNGAN ANTARA MODERATE EXERCISE DAN SIKLUS MENSTRUASI TERATUR PADA REMAJA - Perestroika, Grhasta Dian; Argaheni, Niken Bayu; Prastika, Dewi Andang; Syarifah, Syarifah (Ensiklopedia of Journal, 2024)
By conducting a bibliometric analysis based on Scopus data from 2013 to 2023, this study provide a comprehensive overview of the research landscape concerning the interaction between moderate exercise and regular menstrual cycles in adolescents. This study aims to inform researchers, educators, clinicians, and policymakers about existing knowledge, identify research gaps, and guide future investigations. The Scopus database was utilized for data collection and analysis. The keywords used for the search included "exercise OR physical activity AND menstrual cycles AND adolescents".The Scopus website and VOS Viewer were utilized as the bibliometric analysis tools to conduct an analysis of the collected data. This analysis included examining the data distribution from the literature in Scopus, as well as visualizing the semantic network of documents. The consistent fluctuation in document numbers can be observed from year to year. The journal "Nutrients" continues to contribute up to the present time. Document distribution is predominantly in the field of medicine, followed by biochemistry and nursing. This collectively illuminates research evolution, source importance, and global collaboration in studying exercise's relation to the adolescent menstrual cycle. In conclusion, the continuous fluctuations, enduring input from "Nutrients," medical field's dominance in subject distribution, and the United States' pivotal role emphasize the urgency of investigating light exercise's link to menstrual cycles in adolescents due to its complexity.